Evaluation of Aerodynamic and Sonic Boom Performance of Supersonic Transport Aircrafts with Multiple Wing Configurations - Wataru Yamazaki; Shu Ishida (Aerospace)
In this study, two-dimensional airfoil shapes obtained in aerodynamic optimizations are converted to three-dimensional wing models and then their aerodynamic and sonic boom performance are evaluated. The airfoil shapes analyzed are the diamond, Busemann, new supersonic biplane (NSB), and triplane airfoil configurations. The NSB is a modified version of the Busemann biplane airfoil proposed in previous studies. The triplane airfoil configuration is obtained in this study by maximizing the lift-to-drag ratio using an aerodynamic topology optimization method. Based on the obtained two-dimensional airfoil shapes, three-dimensional multiple (biplane/triplane) wing configurations are designed. The aerodynamic and sonic boom performance of these configurations is evaluated in detail through three-dimensional flow analyses as well as acoustic propagation analyses. The aerodynamic superiority of the multiple wing configurations is confirmed in this study.